Methylene blue reduces the serum levels of interleukin-6 and inhibits STAT3 activation in the brain and the skin of lipopolysaccharide-administered mice - Li, Yujia; Ying, Weihai (Frontiers in Immunology, 2023)
It is valuable to search for novel and economical agents for inhibiting STAT3 activation and blocking increases in IL-6 levels, due to the important roles of STAT3 and IL-6 in inflammation. Since Methylene Blue (MB) has shown therapeutical potential for multiple diseases, it has become increasingly important to investigate the mechanisms underlying the effects of MB on inflammation. Using a mouse model of lipopolysaccharide (LPS)-induced inflammation, we investigated the mechanisms underlying the effects of MB on inflammation, obtaining the following findings: First, MB administration attenuated the LPS-induced increases in the serum levels of IL-6; second, MB administration attenuated LPS-induced STAT3 activation of the brain; and third, MB administration attenuated LPS-induced STAT3 activation of the skin. Collectively, our study has suggested that MB administration can decrease the levels of IL-6 and STAT3 activation - two important factors in inflammation. Since MB is a clinically used and relatively economical drug, our findings have suggested therapeutic potential of MB for multiple inflammation-associated diseases due to its effects on STAT3 activation and IL-6 levels.